Cobalt sulfide nanoparticles restricted in 3D hollow cobalt tungstate nitrogen-doped carbon frameworks incubating stable interfaces for Li-ion storage. (1st November 2022) - Zheng, Yun; Xu, Yang; Guo, Junpo; Li, Jianding; Shen, Jingjun; Guo, Yan; Bao, Xiaozhi; Huang, Yike; Zhang, Qi; Xu, Jincheng; Wu, Jue; Ian, Hou; et al.
Highlights: Hierarchical nanostructure Co9 S8 @CoWO4 /nitrogen-doped carbon was obtained based on Ostwald ripening mechanism. Ingenious yolk-shell configuration boosts Li-ion transport and buffers volume expansion during lithiation/delithiation. Co9 S8 @CoWO4 /nitrogen-doped carbon anode delivers an ultrahigh specific capacity (1053 mAh·g −1 at 500 mA·g −1 ). In-situ EIS and Ex-situ SEM were conducted to confirm the successful incubating of stable interfaces. Abstract: Hierarchical nanostructures that comprise multiple tiers of structural subunits and diverse chemical components can provide more active storage sites and relieve the micro-strain due to volumetric change than solid structures in LIBs. In this work, we designed the facile preparation of a yolk-shell structure based on Ostwald ripening for steady lithium-ion storage with Co9 S8 @CoWO4 /nitrogen-doped carbon nanohybrids (YS-Co9 S8 @CoWO4 -NC) as anodes. This yolk-shell configuration design not only accelerated the diffusion of lithium-ion during the lithiation process but also constructed stable interfaces for achieving more steady cycling. It consequently delivered long cycle stability (780 mAh·g −1 after 250 cycles at 1000 mA·g −1 ) and excellent rate capacities (1023, 767 mAh·g −1 at 100, 2000 mA·g −1, respectively). Furthermore, in-situ electrochemical impedance spectroscopy was successfully implemented to monitor interface properties by simultaneously recording the impedance during discharging and charging processes. The incubating of stable interfacial layers was further confirmed by ex-situ SEM. These results fully affirmed the contribution of hierarchical nanostructures to the construction of stable interfaces, achieving long cycle Li-ion storage. Graphical abstract: Image, graphical abstract